Sharing schadenfreude and late adolescents' self-esteem: does sharing schadenfreude of a deserved misfortune enhance self-esteem?. Issue 4 (2nd October 2019) - Watanabe, Hitomi
ABSTRACT: This study examined the effects of sharing schadenfreude with friends on late adolescents' self-esteem. University students (242 men; 238 women) were presented with scenarios depicting a deserved failure of a superior rival classmate and sharing schadenfreude. Participants' state self-esteem was measured both before the rival's misfortune and after sharing schadenfreude and was compared with that of participants presented with the non-sharing scenario. Whereas experiencing schadenfreude enhanced late adolescents' state self-esteem regardless of the level of envy toward the rival, sharing schadenfreude with a best friend was not associated with further increases in self-esteem. When discussing the very well-deserved misfortune of others, the listener will likely react similarly to the expresser; thus, expressing schadenfreude may not bring about a sense of being understood and accepted by friends.